2021
DOI: 10.1111/1346-8138.15728
|View full text |Cite
|
Sign up to set email alerts
|

Vulvar hidradenitis suppurativa: Clinical cross‐sectional study of 25 patients

Abstract: Hidradenitis suppurativa (HS) is a chronic inflammatory condition characterized by repeated episodes of painful and disabling lesions in apocrine gland-bearing areas. 1 Its diagnosis relies on Dessau criteria. 2 Several types of lesions are described in the disease, namely nodules, abscesses, fistulas, cords, pustules, open comedos, and multiple pyogenic granulomas. 3 In 2013, Canoui-Poitrine et al 4 described a phenotypic classification which correlates with different degree of severity: Latent Class 1 (LC1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…López-Llunell et al studied 25 patients with VHS and found that patients had late onset of disease. The average BMI of VHS was normal (HS with VHS: 23.2 kg/m 2 vs. HS without: VHS 28.6 kg/m 2 ) [ 73 ]. A nationwide cohort analysis in Denmark investigated medication of HS patients [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…López-Llunell et al studied 25 patients with VHS and found that patients had late onset of disease. The average BMI of VHS was normal (HS with VHS: 23.2 kg/m 2 vs. HS without: VHS 28.6 kg/m 2 ) [ 73 ]. A nationwide cohort analysis in Denmark investigated medication of HS patients [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the current data do not allow any clear conclusions to be drawn about thyroid function in HS. HS with vulva involvement was significantly associated with thyroid disease [ 73 ]. The reasons for this association are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Vulvar hidradenitis suppurativa is a highly rare diagnosis with limited reports on literature. 7 Here, we report a confirmed case of hidradenitis suppurativa limited to vulva which was initially diagnosed and managed as cutaneous endometriosis.…”
Section: Introductionmentioning
confidence: 90%
“…5,6 Vulvar hidradenitis suppurativa is a highly rare diagnosis with limited reports on literature. 7…”
Section: Introductionmentioning
confidence: 99%
“…The global prevalence of HS has been reported in the 0.00033–4.1% range [ 5 , 6 ]. The exact etiology and pathogenesis of HS remains unclear [ 7 , 8 ]. The cause of follicular plugging is still under debate, although immune dysregulation, genetic factors, hormonal fluctuation, and environmental risk factors are thought to play a role [ 7 ].…”
Section: Introductionmentioning
confidence: 99%